Integrated home security system :Module on mobile application - Muhammad Izzat, Ramli (2010)
Home security system is needed for occupants' convenience and safety. Nowadays, there is lot of burglary happening across the city, the reason is no one helping or getting late for help. Sometimes, guard in housing area also not helping because of the big area housing environment. Nowadays, Malaysian still uses old technology alarm for their home security. How people react for the alarm? Can the guard in housing area hear it? For this paper, I have design and implementing a security system for home using Bluetooth and SMS notification which is smart in helping owner to get helps from neighbor, friend, police station or guard in housing area faster. The user can choose the recipient number from contact's phonebook and set SMS by self. This system was implemented in J2ME to operate in mobile.